Kepercayaan Masyarakat dalam Pemilihan Umum Serentak Tahun 2019 Pada Komisi Pemilihan Umum (KPU) Kota Palembang (Studi Kasus Kecamatan Ilir Timur II, Gandus, Jakabaring) - Andini, Yunita (Program Studi Politik Islam Universitas Islam Negeri Raden Fatah Palembang, 2020)
This research is related to Simultaneous General Election in 2019 which mainly focused on the research is to know the level of public trust in the General Election Commission (KPU) in carrying out General Elections and the factors that influence the level of trust that objectively referred to General Elections Commission (KPU) of Palembang City. In this research used the Mc. Knight theories of trust regarding the belief formation model was built initially before the parties had time to get to know each other through interactions and transactions. In the Mc. Knight theory, there are two concepts of interpersonal trust or trust intention and favorable trust such as virtue, integrity, competence, predictability and factors of the second trust, namely rational factors and relational factors. This type of research uses qualitative descriptive method with case study method in which data collected through interview and documentation techniques with analyzing from collecting data, reducing data, presenting data to the drawing conclusions. The source of the data in this study is how the community thinks about trust in the Elections Commission (KPU). The results of this study showed that after conducting General Elections there was a problem at the polling station (TPS) at Ilir Timur II District, Gandus, Jakabaring in Palembang City. Not only that, their trust in the Election Commission (KPU) of Palembang City was reduced which influenced by two factors i.e., firstly, Rational factors in which the Election Commission (KPU) has had commissioners in the general election with the appointed position and electoral district, Secondly, Relational factor ensures that commissioner officials can be elected through the experience of strong political institutions. Ultimately, for the next General Elections will be increased by the General Election Commission (KPU) employees in the Palembang City.